2015
DOI: 10.1103/physrevx.5.041031
|View full text |Cite
|
Sign up to set email alerts
|

Dual Dirac Liquid on the Surface of the Electron Topological Insulator

Abstract: We discuss a non-Fermi liquid gapless metallic surface state of the topological band insulator. It has an odd number of gapless Dirac fermions coupled to a noncompact Uð1Þ gauge field. This can be viewed as a vortex dual to the conventional Dirac fermion surface state. This surface duality is a reflection of a bulk dual description discussed recently for the gauged topological insulator. All the other known surface states can be conveniently accessed from the dual Dirac liquid, including the surface quantum Ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
321
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(329 citation statements)
references
References 45 publications
(76 reference statements)
8
321
0
Order By: Relevance
“…These dualities have been the subject of recent attention from a variety of viewpoints. For the special case N = k = N f = 1, these dualities are related to the surface states of time-reversal invariant topological insulators and the fractional quantum Hall effect at half filling [10][11][12][13], lead to a web of dualities [14][15][16][17], and can even be proven on the lattice [18]. They are crucial actors in mapping out the phase diagram of QCD 3 as well as some of its cousins.…”
Section: Jhep01(2018)031mentioning
confidence: 99%
“…These dualities have been the subject of recent attention from a variety of viewpoints. For the special case N = k = N f = 1, these dualities are related to the surface states of time-reversal invariant topological insulators and the fractional quantum Hall effect at half filling [10][11][12][13], lead to a web of dualities [14][15][16][17], and can even be proven on the lattice [18]. They are crucial actors in mapping out the phase diagram of QCD 3 as well as some of its cousins.…”
Section: Jhep01(2018)031mentioning
confidence: 99%
“…Recently, several authors have suggested that flux attachment also holds for relativistic theories [74][75][76][77][78][79][80]. For example, a map exists between the Dirac fermion and complex scalar theories, both including self-interactions, with the boson coupled to the Chern-Simons field for changing statistics [79,80].…”
Section: Jhep05(2017)135mentioning
confidence: 99%
“…In the presence of a boundary, this 3 + 1-dimensional "symmetry-enriched" electric-magnetic duality implies interesting and nontrivial dualities between 2 + 1-dimensional quantum field theories [32][33][34][35]. This line of thinking has proven to be very powerful in studying difficult problems in strong correlation physics in two space dimensions.…”
Section: Introductionmentioning
confidence: 99%